2020
DOI: 10.1126/science.aba8347
|View full text |Cite
|
Sign up to set email alerts
|

Extensive heterogeneity in somatic mutation and selection in the human bladder

Abstract: The extent of somatic mutation and clonal selection in the human bladder remains unknown. We sequenced 2097 bladder microbiopsies from 20 individuals using targeted (n = 1914 microbiopsies), whole-exome (n = 655), and whole-genome (n = 88) sequencing. We found widespread positive selection in 17 genes. Chromatin remodeling genes were frequently mutated, whereas mutations were absent in several major bladder cancer genes. There was extensive interindividual variation in selection, with different driver genes do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
195
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 243 publications
(211 citation statements)
references
References 73 publications
15
195
1
Order By: Relevance
“…Compared to somatic mutations, CNAs are relatively rare and less extensive in the normal tissues from different organs, consistent with previous analyses 5,6,14,15 . In our study, liver samples harbored high mutational burdens coupled with obvious clonal expansions, however, CNAs were seldomly seen across the entire genome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to somatic mutations, CNAs are relatively rare and less extensive in the normal tissues from different organs, consistent with previous analyses 5,6,14,15 . In our study, liver samples harbored high mutational burdens coupled with obvious clonal expansions, however, CNAs were seldomly seen across the entire genome.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have revealed the somatic mutation landscape of different normal human tissues, including the skin 3,4 , esophagus 5,6 , colon and rectum 7 , liver 8 , endometrial epithelium 9 , bronchia 10 , brain 11,12 , embryo 13 , urothelium 14,15 , and blood cells 16,17 , mostly through deep DNA sequencing of biopsied tissue samples. Other studies have implemented bioinformatic algorithms to detect somatic mutations from RNA sequencing data of normal human tissues 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Using multiple samples from the same individuals, we have compared clonal structures, mutation rates and mutational signatures across an extensive range of normal cell types, substantially extending results from previous studies 2,911,13,45,46 . Our results revealed the extent of variation in clonal dynamics across tissues.…”
Section: Discussionmentioning
confidence: 60%
“…Patches of cells dissected from seminiferous tubules of the testis were frequently monoclonal, indicating that they arise from single spermatogonial stem cells. The mutation burdens of these germ cell clones were ~27 fold lower than colorectal crypts from the same individuals and their mutation burdens accumulated with age in a linear manner at 2.02 mutations/year (CI95% 1.83-2.42), lower than all other somatic cells thus far estimated 2,911,13,45,46 . How the male germline achieves this low mutation rate has remained elusive.…”
Section: Discussionmentioning
confidence: 84%
“…It should be noted that SigProfilerExtractor provides extensive output for the interrogated total (vi) to exome downsampling of all 88 whole-genome sequenced microbiopsies of histologically normal urothelium 33 . In all cases, the mutational catalogues of each samples were taken from the respective original publications.…”
Section: Module 7: Outputting and Plotting Of Analysis Resultsmentioning
confidence: 99%